Application of Fractal Geometry to Study the Geological Structure of the Zarin Plain (Plain Razak) - Nia, Khadijeh Faridi; Teymoorian, Asghar; Babaei, Mojtaba (International Journal of Geography and Geology, 2014)
One of the most important steps to obtain the specified density Bouguer anomaly corrections for the topography of the page Bouguer is the most commonly used way in which the relationship between topography and Bouguer anomaly in the method assumes that topography of the rigid shell instead Isoztasi balance is maintained. The method to determine the density of Bouguer provided by fractal analyze these are the lowest density dependence the topography of the area is considered as the optimal density and the fractal relationship to the topography of the fractal dimension using the Bouguer anomaly.